Human resources and business performance: Findings, unanswered questions, and an alternative approach - Barry Gerhart (Management Revue, 2005)
In 1996, Becker and Gerhart noted that much of the work on human resources (HR) and performance had traditionally been conducted at the individual level of analysis. However, in the 1990s, empirical research on HR and performance increasingly moved to the plant/unit and firm level of analysis with a new emphasis on understanding how HR practices influence business performance at these higher levels. In the present article, I describe the empirical findings of this evolving literature, unanswered questions, and an approach to the issue that differs from what has come to be the typical approach over the past 10 years or so.
Keywords: 650; human resources; performance; employee relations; employee attitudes; methodology; Humanressourcen; Betriebsklima; Unternehmenserfolg; Theorie